Photocatalytic Neophyl Rearrangement and Reduction of Distal Carbon Radicals by Iminyl Radical‐Mediated C−C Bond Cleavage. Issue 18 (2nd August 2018) - Yu, Xiao‐Ye; Wang, Peng‐Zi; Yan, Dong‐Mei; Lu, Bin; Chen, Jia‐Rong; Xiao, Wen‐Jing
Abstract: The control of selectivity in the reactions of the highly reactive open‐shell carbon radicals is an attractive but often challenging task. Building on the strategy of photoinduced iminyl radical‐mediated C−C bond cleavage, we have developed photocatalytic neophyl rearrangement and reduction of distal carbon radicals under visible light irradiation of O ‐acyl oximes. This mild protocol tolerates a wide range of readily available O ‐acyl oximes, enabling facile synthesis of diversely substituted α, β ‐unsaturated nitriles and β ‐functionalized saturated nitriles in a highly selective manner. Abstract :